Ethical Climate, Moral Reasoning, and Accounting Fraud: A Systematic Literature Review - Flowrent Aprilianz; Yusnaini Yusnaini (CV. ITTC INDONESIA, 2026)
This study aims to systematically analyze the role of ethical climate and moral reasoning in accounting fraud through a Systematic Literature Review (SLR) approach. This topic is important because accounting fraud is influenced not only by weak internal control systems, but also by the ethical environment within an organization and the quality of an individual’s moral reasoning. The literature search was conducted through Google Scholar, Garuda, SINTA, and Scopus databases with the assistance of Publish or Perish using the keywords ethical climate, moral reasoning, and accounting fraud. The findings show that ethical climate plays a role in reducing accounting fraud, although its effect tends to be indirect and contextual, particularly through strengthening whistleblowing, fraud prevention, and limiting the pressure and opportunity that may encourage fraudulent behavior. Meanwhile, moral reasoning demonstrates a more consistent relationship, indicating that the higher an individual’s moral reasoning, the lower the tendency to engage in accounting fraud. These findings confirm that the prevention of accounting fraud requires the integration of a strong organizational ethical climate and high individual moral quality. This study implies that fraud prevention efforts should not rely solely on formal control systems, but should also be supported by strengthening the organization’s ethical culture and developing the moral reasoning of human resources.